2015
DOI: 10.1002/jbm.b.33592
|View full text |Cite
|
Sign up to set email alerts
|

Protein adsorption, platelet adhesion, and bacterial adhesion to polyethylene-glycol-textured polyurethane biomaterial surfaces

Abstract: Traditional strategies for surface modification to enhance the biocompatibility of biomaterials often focus on a single route utilizing either chemical or physical approaches. This study combines the chemical and physical treatments as applied to poly(urethane urea) (PUU) biomaterials to enhance biocompatibility at the interface for inhibiting platelet-related thrombosis or bacterial adhesion-induced microbial infections. PUU films were first textured with submicron patterns by a soft lithography two-stage rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 72 publications
1
29
0
Order By: Relevance
“…More recently, research efforts have been focused on either the use of natural compounds with anti-biofilm properties [14][15][16][17], or on the development of intrinsically antimicrobial and antifouling materials, by either physical or chemical technological approaches [17][18][19][20]. Physical approaches mainly consist of developing micro-or nano-scale surface texturing in order to affect bacterial adhesiveness, growth, and more in general, biofilm formation [21][22][23][24]. Chemical approaches, instead, mainly involve the functionalization of material surfaces, to meet some criteria that are well-recognized to confer repelling activities, which include strong hydrophilicity, neutral charge, and the presence of groups that are able to establish hydrogen bonds [25].Polyethylene glycol (PEG) is undoubtedly, the most closely investigated antifouling polymer, as it meets all of the criteria listed above [26].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, research efforts have been focused on either the use of natural compounds with anti-biofilm properties [14][15][16][17], or on the development of intrinsically antimicrobial and antifouling materials, by either physical or chemical technological approaches [17][18][19][20]. Physical approaches mainly consist of developing micro-or nano-scale surface texturing in order to affect bacterial adhesiveness, growth, and more in general, biofilm formation [21][22][23][24]. Chemical approaches, instead, mainly involve the functionalization of material surfaces, to meet some criteria that are well-recognized to confer repelling activities, which include strong hydrophilicity, neutral charge, and the presence of groups that are able to establish hydrogen bonds [25].Polyethylene glycol (PEG) is undoubtedly, the most closely investigated antifouling polymer, as it meets all of the criteria listed above [26].…”
mentioning
confidence: 99%
“…Most of such PEG-containing PUs were studied in terms of bio-and hemo-compatibility properties, through the study of polymer affinity towards biomolecules such as albumin, fibrinogen, or heparin [35][36][37][38][39]. Only recently, a series of studies has been carried out to investigate the influence of PEG-containing PUs on microbial adhesiveness [22,40,41]. The few positive datasets available so far encourage further experimentations in order to uniquely confirm PEG as a potent antibacterial fouling agent for polyurethane surfaces.In this study, a segmented carboxylated polyurethane, obtained by the polymerization of an aromatic di-isocianate, an ether macrodiol, and a low molecular weight diol displaying a carboxylic group, was functionalized with PEG by a Steglich esterification reaction, in order to improve polymer-antifouling abilities.…”
mentioning
confidence: 99%
“…Human serum albumin and fibrinogen are two of the most abundant proteins in the human blood and exert opposite effects on the thrombogenicity of a surface. HSA adsorption lowers thrombogenicity, being inert towards platelets receptors, and reduces both the number of adhered platelets and the degree of platelet activation [34,35]. FBG, on the contrary offers platelet-binding sites and is responsible for platelets activation and aggregation [36].…”
Section: Resultsmentioning
confidence: 99%
“…Biological structure is often linked to function and suggests that surface topography may serve a critical role in antifouling of a system. In prior studies, nanoscale static topography with high density structure, related to the material composition, has been shown to reduce platelet adhesion and activation as well as support endothelial growth and alignment (Koh et al, 2010;Uttayarat et al, 2010;Xu and Siedlecki, 2017). In contrast, Pocivavsek et al (2008Pocivavsek et al ( , 2018Pocivavsek et al ( , 2019 reported a biophysical analysis of a possible novel mechanism of surface cleansing in nature and in innovation, namely that of a dynamic "wrinkled surface" or dynamic macro-topography.…”
Section: Introductionmentioning
confidence: 99%